2020
DOI: 10.1155/2020/7538232
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Standardized Extract of Propolis (EPP‐AF®) in Healthy Volunteers: A “Before and After” Clinical Study

Abstract: Background. Propolis is rich in polyphenols, especially flavonoids and phenolic acids, and has significant antioxidant activity, shown mainly in “in vitro” studies. Objective. The aim of this study was to evaluate the antioxidant efficacy and safety of a standardized propolis extract in healthy volunteers. Design. A two-phase sequential, open-label, nonrandomized, before and after clinical trial. Methods. Healthy participants received two EPP-AF® doses (375 and 750 mg/d, P.O, tid) during 7 ± 2 days, starting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
(42 reference statements)
1
18
0
2
Order By: Relevance
“…Similar data have been documented by other researchers [75,76]. In a human trial study, Diniz et al have reported that the administration of microencapsulated standardized Brazilian green propolis extract (375 and 750 mg/day) during 7 days rose the endogenous enzymatic and nonenzymatic antioxidants and reduced the biomarkers associated with the cellular membrane and DNA damage in healthy young participants [77]. Similarly, Ebeid and coworkers have demonstrated that propolis supplementation (400 mg, 3 times daily) for 10 consecutive days before and 10 days after the radiotherapy session had been able to reduce significantly the DNA oxidative damage of breast cancer patients [78].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 85%
“…Similar data have been documented by other researchers [75,76]. In a human trial study, Diniz et al have reported that the administration of microencapsulated standardized Brazilian green propolis extract (375 and 750 mg/day) during 7 days rose the endogenous enzymatic and nonenzymatic antioxidants and reduced the biomarkers associated with the cellular membrane and DNA damage in healthy young participants [77]. Similarly, Ebeid and coworkers have demonstrated that propolis supplementation (400 mg, 3 times daily) for 10 consecutive days before and 10 days after the radiotherapy session had been able to reduce significantly the DNA oxidative damage of breast cancer patients [78].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 85%
“…In this work, authors denote that the effect of propolis seems to be related to time and gender due to the male population treated with propolis reduce their lipid peroxidation and increase the SOD enzyme activity; whereas the female population evaluated did not present any change associated with the treatment with propolis in the antioxidant parameters evaluated. Another study, reports the antioxidant activity of a standardized extract of propolis in healthy people, in which, the extract increase antioxidant enzymatic capacity significantly, in special, propolis increase the activity of the SOD enzyme in this patients, although authors there is not reported a correlation of this antioxidant activity of propolis with the sex of patients [ 189 ].…”
Section: Discussionmentioning
confidence: 99%
“…Propolis is a resinous substance produced by bees from plant parts and resins that they use to protect the hive. It has antiviral, anti-inflammatory, immunoregulating, antiproteinuric and antioxidant properties 7,17,18,22 . Normally, propolis varies according to climate regions and to the types of plants available 9,19 .…”
Section: Discussionmentioning
confidence: 99%
“…A pertinent objection to wider acceptance of propolis for medicinal use has been that it varies widely in composition and biological activity, according to the plant species that the bees selectively collect bioactive materials from in the different regions of the world 13,14 . In answer to this limitation, a standardized propolis product has been developed 15 and tested in clinical trials 16,17,18 . Given the evidence concerning its biological properties, we hypothesized that propolis could help reduce the clinical impact of COVID-19 without interfering with other treatment options.…”
mentioning
confidence: 99%